System of analysis and management of Power Quality indices in distribution networks - Melo, Guilherme De Azevedo E [UNESP]; De Oliveira, Rodrigo A. N. [UNESP]; De Oliveira, Luis C. O. [UNESP]; De Souza, Júlio Borges [UNESP]; Canesin, Carlos A. [UNESP]; Da Silva, Roberto J. C.; Gouveia, Bernard De S. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents a system (PQGenAnalyzer) for treatment, analysis and management of the main Power Quality (PQ) indices for distribution networks, applied to Eletrobras Distribuição Alagoas-Brazil. The PQ indices are monitored using PQube/PSL devices. The PQGenAnalyzer was developed to operate in server system with data extracted from geo-referenced database of distribution networks (GIS). The PQGenAnalyzer performs the power flow simulation for the distribution network, considering its non-linear loading, allowing data comparisons from the simulations with those obtained from all busbars and sections with the PQube monitors. The PQGenAnalyzer has tools for critical points identification, starting at the substation, considering the busbar voltage levels, as well as their respective Harmonic Contents. Therefore, the PQGenAnalyzer is an extremely important tool for monitoring the distribution networks operation, considering the management of PQ parameters and the corrective actions that must be taken, in order to ensure continuous improvement in these PQ indices.
Keywords: Non-Linear Electric Loads; Power-Flow in Distribution Networks; PQ Management; PQ Monitoring; Smart Grids